The Implementation of the 2013 Curriculum in Teaching Simple Present Continuous Tense through Cooperative Learning at the Eighth Grade Students of SMPN 13 Semarang - Samsudin Samsudin; Muslimin Muslimin (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
This study attempts to describe teacher’s method in implementing of 2013 curriculum. This study used qualitative as the approach and case study as its research design. The subject of this study was eighth grade students of SMPN 13 Semarang. To collect the data, the writer used observation and interview. The result of the study shows that the English teacher used cooperative learning in teaching simple present continuos tense using cooperative technique in implementing 2013 curriculum. He tried to implement the five learning steps of scienctific approach of 2013 curriculum. However, he encountered some problems such as limited time, less competence in implementing 2013 curriculum, unavailablity of workshop or seminar in his school. In other cases, the English teacher only focus on the textbook to give the examples of the material. Whereas, teaching simple present continues tense needs the real examples to make students understand. Therefore, the teacher needs workshop of the implemetation of 2013 curriculum. the authentic example should be used by the teacher to make students understand easily.